(untitled) (Tempo e Argumento, 2023)
From the interior of Febem in Vila Maria, in São Paulo, Anderson Herzer’s autobiographical account emerged in the early 1980s. to have strayed from gender identity and the name stuck to her skin since birth as Sandra Mara. The article analyzes the conditions of emergence of this autobiography, problematizing the practices and disputes so that such a "self-report" was possible in editorial terms at a time when the "minor issue" and forms of resocialization in the press were so much discussed, social movements and state institutions. Through the lenses of Michel Foucault and Judith Butler’s post-structuralism, as well as the intersectional feminist critique of Kimberlé Krenshaw, Carla Akotirene and Adriana Piscitelli, the plots of power and the games of knowledge that acted in the forms of naming and constituting are unraveled. the figure of Herzer, taking the autobiography as a monument crossed by policies of authorship and memory, social demands and editorial policies that (in)feasible the constitution of the report in the way it was bequeathed to us. In this way, the ways of self-constitution are tensioned amidst autobiographies and the politics of subjectivation as constituting cultural patterns, unique performances and modes of existence made visible or not from the perspectives and ways of recognizing or legitimizing differences and dissent in the social field.